Sporadic Creutzfeldt–Jakob disease presenting as epilepsia partialis continua and non‐ictal nystagmus. (10th June 2021) - Cunha, Inês Antunes; Gomes, Inês; Gens, Helena; Guimarães, Susana; Martins, Ana Inês; Bento, Conceição
Abstract: Background and purpose: Creutzfeldt–Jakob disease (CJD) is a rare form of rapidly progressive neurodegenerative disorder. Seizures are uncommon in the early stage of CJD, increasing diagnostic difficulty. Methods: An autopsy‐proven case of CJD presenting initially as an epilepsia partialis continua is reported, in which the initial workup was unremarkable. Retrospectively, the presence of nystagmus, which proved to be non‐epileptic, pointed to a cerebellar lesion before a diagnosis of clinically probable CJD was made. Results: A 70‐year‐old man presented with a 3‐week history of intermittent rhythmic jerking tremors in his left limbs, interfering with his gait. Examination showed left body clonic movements. Electroencephalography revealed an ictal right centroparietal pattern of focal status epilepticus. Video‐oculography revealed right‐beating nystagmus (mean slow phase velocity [SPV] 3.4º/s) in the dark and left‐beating nystagmus (SPV 2.6º/s) in the light, left‐beating nystagmus after head shaking (SPV 4º/s) and during mastoid vibration (SPV 11º/s) and mildly hypoactive horizontal head impulses. Search for occult malignancy, serologies, cerebrospinal fluid analyses, anti‐onconeural antigen, auto‐immune panel and brain magnetic resonance imaging were unrevealing. Rapid neurological decline was observed. Three weeks later, cerebrospinal fluid was positive for 14.3.3 protein, electroencephalography showed generalized periodic sharp wave complexes and brain magnetic resonance imaging revealed diffusion restriction and T2/fluid‐attenuated inversion recovery hyperintensities in the cerebellum, basal ganglia, thalamus and cortex. He died 1 month later. Neuropathological study confirmed the diagnosis of CJD. Conclusion: This case highlights that CJD should be considered in the differential diagnosis of new onset epilepsia partialis continua and that neuro‐ophthalmological examination can be helpful in pointing to early asymmetric cerebellar involvement. Abstract : An atypical presentation of an autopsy‐proven case of sporadic Creutzfeldt–Jakob disease (CJD) is reported, in which the initial workup was unremarkable. Video‐oculography (a) revealed a spontaneous left‐beating nystagmus in the light (middle segment), right gaze with right‐beating nystagmus (upper segment) and left gaze with left‐beating nystagmus (lower segment). Electroencephalography recording (b) revealed an ictal right centroparietal pattern. CJD should be considered in the differential diagnosis of new onset epilepsia partialis continua and the neuro‐ophthalmological examination can be helpful in pointing to early asymmetric cerebellar involvement.